Adopting Dublin Core with modifications: Challenges and requirements to develop a standard metadata for UM Memory - Juhaida, A.R.; Sutarmi, Kasimun; Mohd Faizal, H. (2015)
UM Memory was initiated by the University of Malaya Library to build up digital photo collection. It was officially launched by Royal Professor Ungku A. Aziz on 22 September 2011 and his historical photo in the University was the first online exhibition displayed in UM Memory. The purpose of this initiative is to make the Library photo collection accessible to the public through complete metadata. Metadata of the item must be informative in order to capture the digital user’s interest. Several challenges have been faced by the librarians because no standard has been recorded as a guideline since this project was the pioneer project for historical images repository in the University of Malaya. This paper presents the steps taken by the librarians to produce a proper metadata standard to be used in UM Memory. It compares few established metadata from several institutions worldwide and also discusses the significance of excellence pledge for metadata. Several considerations need to be highlighted to confirm the metadata can represent the images in the portal effectively.